2020
DOI: 10.1038/s41467-020-14830-y
|View full text |Cite
|
Sign up to set email alerts
|

A combined experimental and modelling approach for the Weimberg pathway optimisation

Abstract: The oxidative Weimberg pathway for the five-step pentose degradation to α-ketoglutarate is a key route for sustainable bioconversion of lignocellulosic biomass to added-value products and biofuels. The oxidative pathway from Caulobacter crescentus has been employed in in-vivo metabolic engineering with intact cells and in in-vitro enzyme cascades. The performance of such engineering approaches is often hampered by systems complexity, caused by non-linear kinetics and allosteric regulatory mechanisms. Here we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 57 publications
2
53
1
Order By: Relevance
“…S 1 ) as compared to Cc D-KdpD1, could suggest that the N-terminus for D-KdpD is important to enzyme activity and/or stability, and that the addition of further amino acids N-terminally would impede either. However, in a recent study, N-terminally fused His-tag of Cc KdpD2 (bearing additional 20 amino acids in N-terminus in comparison to C-histag of Cc KdpD2 in this study) showed a magnitude of activity similar to Cc KdpD2 (Shen et al 2020 ). Further analysis using BLAST searches in the NCBI and UniProt database suggest that the previously cloned and characterized Cc D-KdpD1 might be cloned with the wrong start codon (Tai et al 2016 ), since most of the homologs do not show the 58 amino acids extension at the N-terminus.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…S 1 ) as compared to Cc D-KdpD1, could suggest that the N-terminus for D-KdpD is important to enzyme activity and/or stability, and that the addition of further amino acids N-terminally would impede either. However, in a recent study, N-terminally fused His-tag of Cc KdpD2 (bearing additional 20 amino acids in N-terminus in comparison to C-histag of Cc KdpD2 in this study) showed a magnitude of activity similar to Cc KdpD2 (Shen et al 2020 ). Further analysis using BLAST searches in the NCBI and UniProt database suggest that the previously cloned and characterized Cc D-KdpD1 might be cloned with the wrong start codon (Tai et al 2016 ), since most of the homologs do not show the 58 amino acids extension at the N-terminus.…”
Section: Discussionmentioning
confidence: 52%
“…The authors (as well as this study) have demonstrated a higher catalytic efficiency for Px D-KdpD than for Cc D-KdpD1 (Table 2 ). Furthermore, in the recent study combining enzymatic and modeling approach, the authors were able to predict and simulate the activity of all five Weimberg enzymes, including Cc D-KdpD2 in cell-free extracts based on their kinetic model (Shen et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…xylose. BT synthesis from xylose is more attractive than BT synthesis from glucose-derived malate because of the 100% theoretical yield of the former xylose pathway (Li, Cai, Li, & Zhang, 2015;Shen et al, 2020;Z. Zhao, Xian, Liu, & Zhao, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Broadly, the challenge of optimizing engineered biological systems increases exponentially with the number of components involved. [1][2][3] This challenge does not lie primarily in physical construction of DNA sequences and so forth, because any difficulties here increase only linearly with system size. Rather, it arises because each extra active molecule in a system adds further dimensions to the parameter space in which the finished system will operate.…”
Section: Introductionmentioning
confidence: 99%